2022
DOI: 10.1088/1361-651x/ac3dd1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Payne effect on basis of linearization of a visco-hyperelastic model

Abstract: The present work concerns the modeling of the Payne effect in nonlinear viscoelasticity. This effect is a characteristic property of filled elastomers. Indeed, under cyclic loading of increasing amplitude, a decrease is shown in the storage modulus and a peak in the loss modulus. In this study, the Payne effect is assumed to arise from a change of the material microstructure, i.e., the thixotropy. The so-called intrinsic time or shift time was inferred from solving a differential equation that represents the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Payne found that the dynamic moduli of carbon blackfilled rubber change with strain amplitude, and this strain amplitude correlation is also known as the Payne effect [1,2]. Some constitutive models have been put forward to characterize the Payne effect well [3][4][5][6]. Among them, the Kraus model [7] is the famous phenomenological model to represent the Payne effect on a physical level, which has been modified by Ulmer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Payne found that the dynamic moduli of carbon blackfilled rubber change with strain amplitude, and this strain amplitude correlation is also known as the Payne effect [1,2]. Some constitutive models have been put forward to characterize the Payne effect well [3][4][5][6]. Among them, the Kraus model [7] is the famous phenomenological model to represent the Payne effect on a physical level, which has been modified by Ulmer [8].…”
Section: Introductionmentioning
confidence: 99%